The determination of the 17-hidrocorticoides free in plasma at sea level and chronic hypoxia - Subauste P., Carlos (2015)
Plasma determination is made at baseline of 17-hydroxycorticoids free in 39 subjects sea level (Lima) and 30 subjects in chronic hypoxia (Morococha 4,540 mts.). In the group of sea level Mean ± SD was 13.7 ± 4 .09 ug% with extreme values of 6.8 ug ug% and 23.2%. In the group height Mean ± S.D. was 18.7 ± 7.93 ug% with extreme values of 5.1 and 33.8%. The differences between the means of both groups have statistical significance. Accepting the possibility of unspecified pigments can distort these determinations in the group of high, also it raises the possibility that higher values of this group are actually translation of chronic stress by chronic hypoxia.